IBN AL-HAYTHAM ET LE MOUVEMENT D'ENROULEMENT. Issue 1 (March 2020) - Rashed, Roshdi; Penchèvre, Erwan
Abstract: In the Almagest, Ptolemy proposed the concept of winding motion, especially to explain planetary latitudes. Ibn al-Haytham (beginning 11th c.) wrote a treatise entitled Fī ḥarakat al-iltifāf, "Concerning the winding motion". An anonymous scholar wrote a refutation of this treatise. Both texts have been lost; but the answer of Ibn al-Haytham has survived: Fī ḥall šukūk ḥarakat al-iltifāf, "The resolution of doubts concerning the winding motion". There he reminds us of his model and gives us a more detailed explanation. We give here a critical edition, translation and commentary of this answer, as well as an edition and translation of some related excerpts from Ptolemy's Planetary Hypotheses and Quṭb al-Dīn al-Shīrāzī's Nihāyat al-idrāk (13th c.).